A double‐blind placebo‐controlled trial of N‐acetylcysteine in the treatment of cocaine dependence. (15th May 2013) - LaRowe, Steven D.; Kalivas, Peter W.; Nicholas, Joyce S.; Randall, Patrick K.; Mardikian, Pascale N.; Malcolm, Robert. J.
<x xml:space="preserve">Abstract</x> Background There remains no FDA approved medication for the treatment of cocaine dependence. Preclinical studies and early pilot clinical investigations have suggested that N‐acetylcysteine (NAC) may be useful in the treatment of the disorder. Objective The present report assessed the efficacy of NAC in the treatment of cocaine dependence. Methods Cocaine‐dependent volunteers (n = 111) were randomized to receive daily doses of 1, 200 mg of NAC, 2, 400 mg of NAC, or placebo. Participants were followed for 8 weeks (up to three visits weekly). At each of these visits, urine samples were collected, along with self‐reports of cocaine use. Urine samples were assessed for quantitative levels of benzoylecognine (ie, cocaine metabolite). Results Overall, the primary results for the clinical trial were negative. However, when considering only subjects who entered the trial having already achieved abstinence, results favored the 2, 400 mg NAC group relative to placebo, with the 2, 400 mg group having longer times to relapse and lower craving ratings. Conclusion While the present trial failed to demonstrate that NAC reduces cocaine use in cocaine‐dependent individuals actively using, there was some evidence it prevented return to cocaine use in individuals who had already achieved abstinence from cocaine. Scientific Significance N‐acetylcysteine may be useful as a relapse prevention agent in abstinent cocaine‐dependent individuals. (Am J Addict 2013;22:443–452)